Tourism experiences in low-density territories: the case of the Historical Village of Trancoso - Castanheira, Maria João Guedes (2022)
In a context of high competitiveness between destinations, the promotion of tourism based on authenticity, uniqueness, and enhancement of the tourist experience has been considered an approach that can play a relevant role in the development of low-density peripheral territories. The investment in tourism experiences can be an adequate strategy for the development of low-density territories. The main purpose of this study is to analyse the importance of investment in tourism experiences at the Portuguese Historical Village of Trancoso. The methodology includes the application of questionnaires which were applied to Trancoso visitors and interviews with three groups of stakeholders: researchers and specialists, local community, and responsible for territory management. The results show that the availability of specific tourism experiences products is low in the studied destination. However, these products were found to be considered strategic by visitors and stakeholders. The main contributions from this study are the need to increase in diversification and differentiation of products, using endogenous resources, and engaging the local community. This strategy has the potential for providing a more authentic and fulfilling tourism experience to visitors while contributing to the economic and social conditions of the community as a whole.